2015
DOI: 10.11152/mu.2013.2066.173.mmg
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of desmoplatic fibroma of the mandible; a case report.

Abstract: Desmoplastic fibroma (DF) is a very rare bone tumor, classified as a benign lesion. It might be locally a very aggressive tumor with a high rate of recurrence after surgical resection. We present a case of a 3-year and 6 month-old patient, with mandibular desmoplastic fibroma. The clinical, imaging, histological findings and surgical treatment are discussed and, also, a brief review of the literature of DF is presented. The purpose of this case report is to emphasize the particularity of the case, ultrasound f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This finding is in agreement with Mohammadi et al (12) Due to the aggressive behavior of DF, different treatment protocols have been proposed. (13) Higher recurrence rate (37%-72%) of DF after enucleation and curettage was reported by Gersak et al (14) While Böhm et al, showed no recurrences after resection with wide surgical margins. (15) Radiotherapy is not recommended due to the lesion's potential for mutagenic transformation into fibrosarcoma.…”
Section: Case Reportmentioning
confidence: 89%
“…This finding is in agreement with Mohammadi et al (12) Due to the aggressive behavior of DF, different treatment protocols have been proposed. (13) Higher recurrence rate (37%-72%) of DF after enucleation and curettage was reported by Gersak et al (14) While Böhm et al, showed no recurrences after resection with wide surgical margins. (15) Radiotherapy is not recommended due to the lesion's potential for mutagenic transformation into fibrosarcoma.…”
Section: Case Reportmentioning
confidence: 89%
“…Anecdotal reports of successful use of radiotherapy in patients with DF are available, though these cases were of DF involving the lower limbs and not the gnathic bones 53 , 54. A wide range of complications have been described in cases of DF ranging from difficulty in mouth opening, extension into the adjacent soft tissue, perineural encasement, loosening of the overlying tooth, dysfunction of the temporomandibular joint, sinusitis, and nasal obstruction 1 , 8 , 13 , 22 , 23 , 25 , 27 , 28 , 32 , 36 , 41 , 42 , 44. All the complications are secondary to the aggressive nature of the tumor and the mass effect.…”
Section: Discussionmentioning
confidence: 99%